Initiating santripreneurship through narrative inquiry: Integration of digital marketing and technical proficiency for pesantren entrepreneurship - Nimasari, Elok Putri; Setiawan, Fery; Gestanti, Rohfin Andria (Universitas Ahmad Dahlan, 2024)
Although entrepreneurship training is commonly conducted for micro, small, and medium enterprises (MSMEs), entrepreneurship training that integrates digital marketing and technical proficiency with a narrative inquiry approach is rarely implemented in Islamic boarding school or pesantren. This narrative inquiry research for community service program aimed to develop and implement an integrated training program that includes excellent service training, local coffee processing, and digital marketing at entrepreneurship-based Islamic boarding schools. Thirteen participants from a pesantren and a entrepreneurship-partner participated in this study. Data were collected from observation and unstructured interviews spanning five months. Drawing on community engagement theory, the findings identified three micro themes: active participation and community involvement; multidisciplinary collaboration and synergy; and empowerment and self-transformation. The contribution of this present study is to provide empirical and practical evidence regarding how community engagement perspective can describe to what extent digital marketing and technical proficiency help micro, small, and medium enterprises in pesantren.